Organizational commitment of emergency physician and its related factors: A national cross-sectional survey in China - Peng, Ke; Han, Xiaotong; Jiang, Nan; An, Rongrong; Lv, Chuanzhu; Yan, Shijiao (Frontiers in Public Health, 2022)
Background Organizational commitment is important for job performance and employee retention. However, studies on the level of organizational commitment and its related factors among emergency physicians in China are scarce. Therefore, this study aimed to identify the factors associated with organizational commitment among emergency physicians in China. Methods A national cross-sectional study was conducted in 2018 among emergency physicians in China. Data were collected from 10,457 emergency physicians using a standard structured anonymous questionnaire, including demographic characteristics, organizational structure factors and work environment factors. A generalized linear model was used to explore the correlation between the independent variables and organizational commitment. Results In this study, 55.3% of emergency physicians reported a moderate level of organizational commitment. The physicians who were male, younger than 40 years old, had a mid-level title and had a lower average monthly income were more likely to show lower organizational commitment levels. Conversely, the organizational commitment was higher among physicians who perceived that promotion is easy and the number of emergency physicians meet their daily work or had not experienced workplace violence in the last year. Conclusions The study showed that organizational commitment among Chinese emergency physicians was moderate and related to gender, age, monthly income, frequency of daily visits, departmental promotion mechanism and workplace violent. Targeted interventions are needed to improve the organizational commitment of emergency physicians in a comprehensive way.